Pengaruh Model Pembelajaran Deep Learning Terhadap Motivasi Belajar Siswa dalam Pendidikan Jasmani - Dani Nurdiana; Anggi Setia Lengkana; Entan Saptani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the effect of the implementation of the Deep Learning learning model on students’ learning motivation in Physical Education, Sports, and Health (PJOK) subjects at the elementary school level. The method used was a quantitative approach with a pre-experimental design of the one-group pretest–posttest type. The sample consisted of 30 students from grades IV–VI selected through random sampling techniques. The research instrument was a learning motivation questionnaire based on a Likert scale. Data analysis was conducted descriptively and inferentially using SPSS through normality tests, paired sample t-tests, and simple linear regression. The results showed that there was an increase in students’ learning motivation after the implementation of the learning model, as indicated by an increase in the average score from 51.53 to 67.03. In addition, there was a significant difference between before and after treatment, as well as a very strong contribution of the learning model to students’ learning motivation. In conclusion, the Deep Learning learning model is effective in improving students’ learning motivation and is recommended as an innovative learning strategy in PJOK learning at the elementary school level. Keywords: Deep Learning, Learning Motivation, Physical Education, Elementary School